P 40. β-γ phase-amplitude coupling during movements in Parkinson's disease. Issue 8 (August 2021) - Gong, R.; Muehlberg, C.; Wegscheider, M.; Knoesche, T.; Classen, J.
Abstract : Question. Enhanced phase amplitude coupling (PAC) between β (13–30 Hz) and broadband γ (50–150 Hz) activities has been found in surface EEG recordings from Parkinson patients at rest [1]. However, the dynamics of PAC during voluntary movement and its relationship with motor impairment of Parkinson"s disease (PD) remain unclear. Methods. Experimental design : We recorded 64-channel EEG signals from 19 PD patients and 20 sex- and age-matched healthy controls at rest, during a repetitive pressing task and during repetitive index finger tapping performed at the patients" own pace and at their fastest pace. Source analysis : We obtained source signals by projecting EEG sensor signals to the individual cortical surfaces. Independent component analysis (ICA) was applied for separating temporally independent subnetworks of each task in each of the 4 brain regions: premotor cortex, primary motor cortex, primary somatosensory cortex and primary somatosensory complex. PAC analysis: Pairwise transient PAC values were calculated among ICA components of each region by zscore-normalized mean vector length [2] in 300ms windows shifted with 50ms time steps in 3s epochs which included an interval of 1s before, and 2s after the onset of the movement. Statistics : We applied a non-parametric three-way ANOVA [3] to test the effects of the disease state, tasks and different brain regions on PAC. For post-hoc testing, a two tailed Wilcoxon ranksum test was used between groups and Wilcoxon signrank test within groups. Results. As expected, maximum tapping rate was lower, and fastest movements were executed more irregularly in patients compared to controls. ANOVA performed on the β-γ PAC values averaged over the entire 3s-epoch revealed an interaction of disease state and tasks ( p < 0.001). Post-hoc testing showed enhanced PAC in patients compared with controls in the resting state ( p = 0.018), in agreement with previous findings, but not in any of the tapping tasks. However, PAC during the pressing task remained elevated in the patients compared to controls ( p = 0.020). Analysis of the temporal dynamics revealed reduction of PAC after the onset of the movement (0–0.25 s) compared with that of the pre-onset period (−0.5 to −0.25 s). The reduction of PAC relative to pre-onset period correlated with the desynchronization in the β power. However, the PAC reduction relative to the resting state was not correlated with the β power reduction. Discussion. Persistence of PAC differences during the pressing task on one hand, and disappearance of PAC differences during the tapping tasks on the other hand, suggest that exaggerated β-broadband γ PAC, as detected in the resting EEG, is not necessarily directly related to impaired motor behavior in PD patients. As our previous findings [1] have shown that abnormal PAC at rest is unrelated to the β band power, partial renormalization of PAC by movement-related β band desynchronization may suggest that mechanisms modulating β activity during movement may selectively affect β activity involved in abnormal coupling. References [1] Gong et al., 2020. Brain. [2] Canolty, R.T., et al., 2006. Science. [3] Kay, M. and Wobbrock, J.O., 2020. Package "ARTool".